0
$\begingroup$

I have the following problem.

If ($a_n$) is a sequence of real numbers such that $ \lim\limits_{n\to \infty}a_n=g$

Show that

$ \lim\limits_{x\to \infty} e^{-x}\sum\limits_{n=0}^\infty a_n \frac{x^n}{n!}=g$

I was wondering if there is an easy way to do this problem, I think I could do it using the definition of the limit of a sequence but because the power series looks so much like the power series for exponential, I feel there should be a better method.

Thanks

$\endgroup$
1
  • $\begingroup$ For any polynomial $p(x), \lim_{x\to\infty}e^{-x}p(x)=0$ $\endgroup$
    – saulspatz
    Apr 15 '18 at 18:10
1
$\begingroup$

Given an $\epsilon>0$, there is some $N$ such that $|a_{n}-g|<\epsilon$ for all $n\geq N$, then for $x>0$ \begin{align*} \left|e^{-x}\sum_{n\geq N}a_{n}\dfrac{x^{n}}{n!}-e^{-x}\sum_{n\geq N}g\dfrac{x^{n}}{n!}\right|\leq e^{-x}\sum_{n\geq N}|a_{n}-g|\dfrac{x^{n}}{n!}\leq \epsilon e^{-x}\sum_{n\geq N}\dfrac{x^{n}}{n!} \end{align*}

but we know that \begin{align*} e^{x}=\sum_{n=0}^{\infty}\dfrac{x^{n}}{n!}\geq\sum_{n\geq N}\dfrac{x^{n}}{n!}>0, \end{align*} so \begin{align*} \left|e^{-x}\sum_{n\geq N}a_{n}\dfrac{x^{n}}{n!}-e^{-x}\sum_{n\geq N}g\dfrac{x^{n}}{n!}\right|\leq\epsilon. \end{align*}

Since \begin{align*} e^{-x}\sum_{n=1}^{\infty}a_{n}\dfrac{x^{n}}{n!}-g&=e^{-x}\sum_{n=1}^{N-1}(a_{n}-g)\dfrac{x^{n}}{n!}+e^{-x}\sum_{n\geq N}a_{n}\dfrac{x^{n}}{n!}-e^{-x}\sum_{n\geq N}a_{n}\dfrac{x^{n}}{n!}, \end{align*} we have \begin{align*} \left|e^{-x}\sum_{n=1}^{\infty}a_{n}\dfrac{x^{n}}{n!}-g \right|\leq e^{-x}\sum_{n=1}^{N-1}|a_{n}-g|\dfrac{x^{n}}{n!}+\epsilon \end{align*} taking $x\rightarrow\infty$, we have \begin{align*} \limsup_{x\rightarrow\infty}\left|e^{-x}\sum_{n=1}^{\infty}a_{n}\dfrac{x^{n}}{n!}-g \right|\leq\epsilon, \end{align*} since $\epsilon>0$ is arbitrary, the assertion follows.

$\endgroup$
1
$\begingroup$

Same ideas as the answer of user284331, but perhaps shorter.

Verify that it's enough to treat the case $g=0.$ ($g$ is weird notation for a limit btw, but fine.) Let $\epsilon>0.$ Then there exists $N$ such that $|a_n|<\epsilon$ for $n>N.$ Thus

$$\tag 1 |e^{-x}\sum_{n=0}^{\infty}a_n\frac{x^n}{n!}| \le |e^{-x}\sum_{n=0}^{N}a_n\frac{x^n}{n!}| + |e^{-x}\sum_{n>N}a_n\frac{x^n}{n!}|.$$

The first expression on the right of $(1)$ $\to 0$ because exponential decay overwhelms polynomial growth as $x\to \infty.$. The second expression on the right of $(1)$, for $x>0,$ is less than

$$\epsilon e^{-x}\sum_{n>N}\frac{x^n}{n!} \le \epsilon e^{-x}\cdot e^{x} = \epsilon.$$

It follows that the $\limsup_{x\to\infty}$ of the left side of $(1)$ is $\le \epsilon.$ Because $\epsilon$ is arbitrarily small, this $\limsup$ equals $0,$ and hence the limit of $(1)$ is $0$ as desired.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.